Flare Synthesis Using Charcoal as a Fuel and Colour Enhancer - Ahmad Hussein Abdul Hamid; Zuraidah Salleh; Noor Farahana Abdul Rahman; Istikamah Subuki; Nurnadia Andenan (International Journal of Integrated Engineering, 2024)
Pyrotechnics have many applications in military and civilian systems, such as signal flares and distress flares. It is mostly used as parachutes or hand-held signal flares to mark particular positions, provide large-area illumination, and provide illumination during emergencies like accidents or for a lost person to attract searchers attention to them. Pyrotechnic flare consists of fuel, oxidizer, and colorant. In this paper, a comparison of the performance and energy output of flares with and without the addition of charcoal is made to determine whether charcoal improves flare efficiency and calorific value as measured by a bomb calorimeter. The composition of flare composition A (FCA) testing number 4 without addition of charcoal that gave the optimum result in terms of flare brightness and ignition time is 73.2 wt% of Sr(NO3)2, 4.9 wt% of NH4ClO4, 12.2 wt% of sulphur, and 9.7 wt% of sawdust. A further analysis of flare composition, with the addition of 0.5 wt% of charcoal, produces brighter red light and a high-intensity flame, including a longer burning time of 90 seconds. Charcoal can not only act as fuel but also improve the red flame colour in flares. A bomb calorimeter is used to measure the heat of combustion for both flares. The heat of combustion of FCA-4 is 798.29 cal/g, while FCB is 664.23 cal/g. Charcoal is successful as a fuel and colour enhancer for flare.